인삼에 함유된 페놀성 성분의 신경세포보호 및 항염증 효과 - 공연희(Yeon Hee Kong); 이영철(Young Chul Lee); 최상윤(Sang Yoon Choi) (Journal of ginseng research, 2009)
The six phenolic-compound (ascorbic acid, maltol, esculetin, p-coumaric acid, cinnamic acid, and quercetin) contents of Panax ginseng C.A. Meyer were determined in this study. The results showed that the ascorbic acid, cinnamic acid, and esculetin contents of Panax ginseng C.A. Meyer are higher than those of the other ingredients. Among these compounds, ascorbic acid and cinnamic acid significantly inhibited LPS-induced nitric oxide production in the RAW 264.7 cells. Cinnamic acid also effectively inhibited the oxidative damages in the human neuroblastoma SH-SY5Y cells. Although this study examined the neuroprotective and anti-inflammatory activities using only one kind of cells, its results suggest that cinnamic acid potently contributes to the neuroprotective and anti-inflammatory properties of Panax ginseng C.A. Meyer. KCI Citation Count: 20